Comparative Analysis of Classification and Factors Causing the Emergence of Bid'ah in the Perspective of Islamic Law Scholars - Muchlis Bahar (International Journal of Science and Society, 2019)
The purpose of this study was to analyze the classification and the causes of their emergence according to Islamic jurists. This research uses qualitative research with descriptive analysis approach. This research uses secondary data and the data collection method used is a literature study. The research was developed by starting the discussion in the perspective of terminology, and redeveloped in the perspective of epistemology and axiology. Based on the previous explanations and descriptions, several conclusions can be drawn, including: 1) Ulama agree that there is Bid'ah in Islamic teachings, but they are different in Understanding the Nature of Bid'ah; 2) Syafi'iyah scholars generally divide Bid'ah into five laws, there are Mandatory, Makruh, Sunnah (Mandubah), Haram and permissible (permissible); and 3) The cause of the emergence of heretical practices is the factor of ignorance (Jahalah) of the religious teachings themselves, because they follow the lust of lust, and because they want to maintain the traditions, culture and customs of their ancestors.